2015
DOI: 10.1039/c5sc00404g
|View full text |Cite
|
Sign up to set email alerts
|

Diverse reactivity of a tricoordinate organoboron L2PhB: (L = oxazol-2-ylidene) towards alkali metal, group 9 metal, and coinage metal precursors

Abstract: The reactivity of a tricoordinate organoboron L2PhB: (L = oxazol-2-ylidene) 1 towards metal precursors and its coordination chemistry were comprehensively studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 85 publications
2
46
0
6
Order By: Relevance
“…The absence of resonances between 0 and −40 ppm in the 1 H NMR spectrum suggests that no hydrido ligand is coordinated in 3 b‐CN . The broad resonance at −37.5 ppm in the 11 B{ 1 H} NMR spectrum is high‐field‐shifted compared to 3‐CO (Table ) and other reported borylene complexes, which is probably due to the different charges of the complexes and the different ligands in trans position to the boron atom: 3‐CO is neutral and has a CO ligand trans to the borylene ligand, whereas in the case of 3 b‐CN the complex is anionic and the stronger σ donor CN − is trans to the boron‐based donor group.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The absence of resonances between 0 and −40 ppm in the 1 H NMR spectrum suggests that no hydrido ligand is coordinated in 3 b‐CN . The broad resonance at −37.5 ppm in the 11 B{ 1 H} NMR spectrum is high‐field‐shifted compared to 3‐CO (Table ) and other reported borylene complexes, which is probably due to the different charges of the complexes and the different ligands in trans position to the boron atom: 3‐CO is neutral and has a CO ligand trans to the borylene ligand, whereas in the case of 3 b‐CN the complex is anionic and the stronger σ donor CN − is trans to the boron‐based donor group.…”
Section: Resultsmentioning
confidence: 80%
“…[17] Althought he reactivity of transition metal boryl and borylene complexes has been discussed extensively, [18][19][20] examples of base-stabilized borylenes and their transition metal complexes are still rare. [21][22][23][24] More interestingly,t he transformation of A into D is in line with af ormal umpolung from aL ewis acidic boron centre, stabilized by ap hosphine (R 3 P!BH 3 ), to aL ewis base that donates electrons to at ransition metal centre (M ! BH{PR 3 } 2 ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In previous studies on the reactivity of 2 , we observed a facile dissociation of one of the oxazol‐2‐ylidenes from the boron center of 2 in its reaction with [IrCl(COD)] 2 . This result prompted us to investigate if similar dissociation could occur in the presence of 1 .…”
Section: Methodsmentioning
confidence: 92%
“…[35] Similarly,species based on oxazol-2-ylidene ligands of formulations L 2 BH were prepared and reported by Kinjo et al [36] Theoxazol-2-ylidene derivative (Me 2 H 2 C 3 N(Me)O) 2 )BPh (25;S cheme 5) can be readily protonated with acid and coordinated to metals to give Cr(CO) 5 ,A uCl, and (NHC)Au + derivatives. [37] More recently, such borylenes have served as precursors to diborylene dications [38] and azaborabutadienes. [39] Scheme 4.…”
Section: Borylenesmentioning
confidence: 99%